The Phenomenon of Mimicry and Collective Memory in Dutch East Indies Soldier Batik Motifs - Christine Claudia Lukman; Monica Hartanti (MOZAIK HUMANIORA, 2022)
Batik motifs are a medium for perpetuating collective memory based on the creator’s point of view of social, cultural, and political conditions of the time. There are differences in meaning and ideology in batik motifs made during colonial and post-colonial era. Using the theory of collective memory and postcolonial mimicry, we want to reveal the differences in meaning and ideology between batik made during the colonial era and after independence. The method in this study is descriptive analysis, using a purposive sample of batik motifs of Dutch East Indies soldiers made by Indo-European, Indo-Arab, Chinese Peranakan, and Bumiputera entrepreneurs. The results show that the Javanese and Lombok War Batiks made during the colonial era are a medium to documentthe collective memory of the colonial community with the ideology that the Dutch East Indies soldiers were brave and great protagonists. Batik Kompeni, contrastingly, is a documentation of the collective memory of the colonized people with the ideology that the Dutch East Indies soldiers were the cruel antagonists. The findings reveal that batik is a medium of collective memory; its creation is closely related to the ideology of the batik creator.